ANALYSIS OF TRANSFER OF SHORT STORY “ROBOHNYA SURAU OUR” BY A.A. NAVIS INTO A DRAMA SCRIPT AND ITS IMPLICATIONS ON LEARNING IN HIGH SCHOOL - Harahap , Andi Syahputra (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2025)
This research is motivated by the lack of students' understanding of the media transfer in Indonesian language learning, as well as the limited use of media/teaching materials. This study aims to describe the process of transferring the media of the short story